Increased 20-HETE Signaling Suppresses Capillary Neurovascular Coupling After Ischemic Stroke in Regions Beyond the Infarct - Li, Zhenzhou; McConnell, Heather L.; Stackhouse, Teresa L.; Pike, Martin M.; Zhang, Wenri; Mishra, Anusha (Frontiers in Cellular Neuroscience, 2021)
Neurovascular coupling, the process by which neuronal activity elicits increases in the local blood supply, is impaired in stroke patients in brain regions outside the infarct. Such impairment may contribute to neurological deterioration over time, but its mechanism is unknown. Using the middle cerebral artery occlusion (MCAO) model of stroke, we show that neuronal activity-evoked capillary dilation is reduced by ~75% in the intact cortical tissue outside the infarct border. This decrease in capillary responsiveness was not explained by a decrease in local neuronal activity or a loss of vascular contractility. Inhibiting synthesis of the vasoconstrictive molecule 20-HETE, either by inhibiting its synthetic enzyme CYP450 omega-hydroxylases or by increasing nitric oxide (NO), which is a natural inhibitor of -hydroxylases, rescued activity-evoked capillary dilation. The capillary dilation unmasked by inhibiting 20-HETE was dependent on PGE2 activation of EP4 receptors, a vasodilatory pathway previously identified in healthy animals. Cortical 20-HETE levels were increased following MCAO, in agreement with data from stroke patients. Inhibition of omega-hydroxylases normalized 20-HETE levels in vivo and increased cerebral blood flow in the peri-infarct cortex. These data identify 20-HETE-dependent vasoconstriction as a mechanism underlying capillary neurovascular coupling impairment after stroke. Our results suggest that the brain’s energy supply may be significantly reduced after stroke in regions previously believed to be asymptomatic and that omega-hydroxylase inhibition may restore healthy neurovascular coupling post-stroke.